Model Pendidikan Guru Berbasis Ke-Bhinekaan Budaya di Indonesia - Al Musanna (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2011)
Teacher education in Indonesia should give more attention to the revitalization of local cultures as the foundation. It is based on the fact that Indonesia is one of the most pluralistic nations in terms of ethnicity and culture. The praxis of culturally responsive teacher education promise solution to bridge the revitalization of local culture and to improve the relevance of teacher education in Indonesian context. Preparing teacher to be a culturally competent teacher can be solutions to marginalization an alienation of many aspects of local culture in Indonesian educational policy.Â ABSTRAKPendidikan guru di Indonesia seyogianya memberi perhatian dalam revitalisasi nilai dan budaya lokal sebagai fondasi pengembangannya, hal ini berdasarkan kenyataan bahwa Indonesia merupakan salah satu negara yang paling pluralistik ditinjau dari suku bangsa dan budaya. Praksis pendidikan guru tanggap budaya atau culturally responsive pedagogy, memberi harapan sebagai jalan keluar untuk menjembatani revitalisasi budaya lokal dan peningkatan relevansi pendidikan guru di tanah air. Penekanan pada pendidikan guru tanggap budaya didasari kenyataan masih terkesampingkannya budaya lokal atau kearifan lokal dalam kebijakan dan kurikulum pendidikan guru di tanah air.